Integrating network structures of different geometric representations. Issue 333 (November 2013) - Dalyot, S.; Dahinden, T.; Schulze, M. J.; Boljen, J.; Sester, M.
Abstract : The availability of reliable vector geodata is increasing rapidly. However, there still exists a lack of appropriate tools and processes for integrated data management and analysis solutions that can handle the diversity of geodata, since structural, geometric and topological aspects affect their data modelling. This paper presents a process that is designed to handle not only existing geometric and topological differences but also structural differences associated with the interoperation and representation of 2D networks. While network structures (such as roads) are usually treated as areal objects in cadastre databases, they are also commonly treated as linear objects in topographic databases. Our integration method is designed to solve not only the positional conflicts in the geodata, but also the existing dissimilarities that are the result of different structural geometric representation primitives used. A localised geometric matching process is introduced for aligning these networks, in which distortions are monitored and quantified locally via sets of specifically selected observation constraints derived from the geometric structures. The aim is to assure that spatial consistency of the 2D geodata is maintained. The outcome presents a significant improvement of the initial state, suggesting a reliable solution for the problem of creating a homogenous unified geodata infrastructure with a statistically sound basis.